Experimental Study on Mechanical Behavior of Lean Cemented Sand and Gravel Material in Unloading and Reloading Paths - Jie Yang; An-yu Yang; Yan-gong Shan; Miao-miao Yang; Jin-lei Zhao; Hang Yu (Advances in Materials Science and Engineering)
Lean cemented sand and gravel (LCSG) materials are subjected to unloading-loading when an LCSG dam is opened for water drainage and then refilled or a roadbed base is subjected to repeated wheel loads. To investigate the behavior of the LCSG materials under loading-unloading, previous studies utilized the complete loading triaxial test. In contrast, in this study, the consolidated drained triaxial tests in the unloading and reloading paths for materials with cementing agent contents of 60 and 100 kg/m3 under different confining pressures, for which each curve generates three loading-unloading cycles, were applied to investigate the unloading and reloading mechanical behavior. Experimental results indicated that the unloading and reloading behavior of the LCSG materials produced stress-strain curves exhibiting a crescent-shaped hysteresis loop, which differs from that exhibited by coarse-grained soil. Although the shape of the crescent-like hysteresis loop was preserved as stress levels increasing, it gradually expanded. Compared with that of the typical triaxial test, the cohesive force and the increasing internal friction angle increased. Further, as the confining pressure increased, the crescent-like hysteresis loops tapered, shear strength increased linearly, and the modulus of resilience increased nonlinearly; the latter’s rate of change, however, decreased. The change in volumetric strain was small during unloading as the stress level changed.